Apoptosis and Autophagy in Picornavirus Infection - Sun, Di; Wen, Xingjian; Wang, Mingshu; Mao, Sai; Cheng, Anchun; Yang, Xiaoyao; Jia, Renyong; Chen, Shun; Yang, Qiao; Wu, Ying; Zhu, Dekang; Liu, Mafeng; et al. (Frontiers in Microbiology, 2019)
Cell death is a fundamental process in maintaining cellular homoeostasis, which can be either accidental or programmed. Programmed cell death depends on the specific signalling pathways, resulting in either lytic or non-lytic morphology. It exists in two primary forms: apoptosis and autophagic cell death. Apoptosis is a non-lytic and selective cell death program, which is executed by caspases in response to non-self or external stimuli. In contrast, autophagy is crucial for maintaining cellular homeostasis via the degradation and recycling of cellular components. These two mechanisms also function in the defence against pathogen attack. However, picornaviruses have evolved to utilize diverse strategies and target critical components to regulate the apoptotic and autophagic processes for optimal replication and the release from the host cell. Although an increasing number of investigations have shown that the apoptosis and autophagy are altered in picornavirus infection, the mechanism by which viruses take advantage of these two processes remains unknown. In this review, we discuss the mechanisms of picornavirus executes cellular apoptosis and autophagy at the molecular level and the relationship between these interactions and viral pathogenesis.